2022
DOI: 10.1590/0074-02760210193
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi genetic diversity: impact on transmission cycles and Chagas disease

Abstract: Trypanosoma cruzi , the agent of Chagas disease (ChD), exhibits remarkable biological and genetic diversity, along with eco-epidemiological complexity. In order to facilitate communication among researchers aiming at the characterisation of biological and epidemiological aspects of T. cruzi , parasite isolates and strains were partitioned into seven discrete typing units (DTUs), TcI-TcVI and TcBat, identifiable by reproducible genotyping protocols. Here we present the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 86 publications
0
41
0
2
Order By: Relevance
“…However, artificial conditions in culture media or even in vivo experimental models represent potential selective pressures for the predominance or elimination of a given parasite population. 6 , 7 This feature had already been observed from the analysis of electrophoretic profiles of DNA from different T. cruzi strains. In one of these experiments, T. cruzi strains were isolated from human hosts by blood culture and inoculated into murine models.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, artificial conditions in culture media or even in vivo experimental models represent potential selective pressures for the predominance or elimination of a given parasite population. 6 , 7 This feature had already been observed from the analysis of electrophoretic profiles of DNA from different T. cruzi strains. In one of these experiments, T. cruzi strains were isolated from human hosts by blood culture and inoculated into murine models.…”
Section: Discussionmentioning
confidence: 57%
“…Correlation of results with complementary information - The correlation of molecular characterisation results with information from patients’ charts, reviews containing distribution maps and graphs of T. cruzi DTUs 4 - 7 , 9 , 33 and a previous research study 32 ) made it possible to better discriminate TcII from TcVI and allowed to suggest that, predominantly, the strains identified by the TcII/VI profile indeed correspond to TcII.…”
Section: Resultsmentioning
confidence: 99%
“…Infections by this TcIDom occur mainly in northern South America, Central America, and Mexico. These isolates have been predominantly associated with cases of cardiomyopathy and are more resistant to benznidazole than other genetic groups [ 14 , 34 , 35 ]. In Mexico, it has been shown that isolates obtained in Querétaro and Ninoa belonging to the TcI genotype can invade the digestive system, in addition to causing damage to the heart [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TSSA is a 14-kDa surface antigen mainly expressed at the trypomastigote stage, capable of transferring sialic acid from host glycoconjugates to β-galactopyranose residues to parasite mucins, thereby generating a surface negative charge that protects the parasite from the alternate complement pathway and opsonization by antibodies. It is also linked with adhesion and invasion to epithelial, neuronal, and glial cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation